Persepsi dan Motivasi Mahasiswa UIN K.H. Abdurrahman Wahid Pekalongan dalam Menggunakan QRIS sebagai Alat Pembayaran Digital - Asti Nur Wilda Ariza; Melly Yanaely Risqi; Aulia Maudy; Gunawan Aji (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze in more depth the perceptions and motivation of UIN KH students. Abdurrahman Wahid Pekalongan on Using QRIS as a Digital Payment Tool. This research uses a qualitative approach by conducting interviews with several informants. The location of the research was at UIN K.H. Abdurrahman Wahid. The data used in this research is primary data. This research uses a purposive sampling technique. The research results show that the use of QRIS by UIN KH students. Abdurrahman Wahid is very effective and efficient in carrying out transactions. QRIS enables faster and easier non-cash transactions, and provides greater security and convenience. Based on the results of interviews, students felt helped by QRIS because it was more practical in making purchases or transactions without cash.